Motor oriented stimulation program during the premature children independent walking acquisition. - Silva, Joyce Karla Machado da; Antonio, Tiago Del; Almeida, Rafaela Martins de; Lima, Mayra Paula de Oliveira; Taniguti, Daniela Licka; Pereira, Vanildo Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Objective: To identify the independent walking acquisition age in premature infants of different gestational ages, distinguish the period of independent walking acquisition among the lower economic classes and compare the independent walking acquisition with data in the literature. Method: This research is characterized as a developmental study. The sample is composed by 21 premature infants of both gender. Assessments and individual data collection were carried out monthly and at the end of the study, at the largest child´s living environment, and that every month the parents/caregivers previously received orientation and demonstration regarding the procedure for applying the stimulation protocol, presented in an illustrative and demonstrative primer. The instrument used for the monthly assessment was the Alberta Infant Motor Scale (AIMS) and the questionnaire of the Associação Brasileira de Empresas e Pesquisa (ABEP), to get the socioeconomic status of the children´s family. The results were analyzed using the Shapiro-Wilk test. Analyzed the age of ability to walk due to the low socioeconomic level through the Kruskal-Wallis test (C1, C2 and D). Results: When comparing the independent walking acquisition age and gestational age, the group with less than 33 weeks of gestational age acquired independent walking later than the group with gestational age between 33-37 weeks. However, it was found that the children average age of independent walking in the study was 14 ± 2 months. Comparing independent walking acquisition age and low economic levels (C1, C2 and D), the group with higher socioeconomic status (C1) acquired independent walking two months before the group with the lowest economic level. Conclusion: influenced positively the motor performance of premature infants in the acquisition of independent walking.